Examining the Negotiation Model of the Disputed Boundary Between Indonesia and Malaysia on Sebatik Island - Nurdin, Amin; Atmoredjo, Sudjito; Arsana, I Made Andi (UI Scholars Hub, 2024)
Sebatik Island is a disputed territory between Indonesia and Malaysia, known as one of the Outstanding Boundary Problems (OBP). The island was divided into two parts by the Dutch and British, based on the 1891 Boundary Convention and the 1915 Boundary Agreement. In 2019, after a long negotiation process, the two countries agreed to re-demarcate the boundary line by planting new boundary pillars. The results of the re-demarcation have not yet been agreed upon by Indonesia and Malaysia, resulting in unclear boundaries of sovereignty and jurisdiction. This study aims to examine the negotiation model of dispute resolution on Sebatik Island. The research methodology employed is doctrinal or normative legal research, which uses both primary and secondary legal data as sources, such as regulations, treaties, court decisions, and doctrines. The study found that the current bottom-up negotiation model has caused delays in reaching an agreement on Sebatik Island. To speed up the settlement of the dispute, it is recommended to modify the model to a top-down approach with a back-to-back or simultaneous mechanism.